2004
DOI: 10.1002/cne.20251
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and cellular localization of neuroactive 5α/3α‐reduced steroid‐synthesizing enzymes in the spinal cord

Abstract: The complementary activities of 5 alpha-reductase (5 alpha-R) and 3 alpha-hydroxysteroid dehydrogenase (3 alpha-HSD) are crucial for the synthesis of neuroactive 5 alpha/3 alpha-reduced steroids, such as 3 alpha-androstanediol, allopregnanolone, and tetrahydrodeoxycorticosterone, which control several important neurophysiological mechanisms through allosteric modulation of gamma-aminobutyric acid type A receptors. Immunocytochemical localization of 3 alpha-HSD in the central nervous system (CNS) has never been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 62 publications
6
67
0
Order By: Relevance
“…The high V max of 5 -R1 endows it with a great capacity to reduce steroids at 5 , and for this reason 5 -R1 has been associated with purely catabolic actions, protecting neurons from excess of glucocorticoids that may induce apoptotic processes (Mahendroo et al 1997, Poletti et al 1998a. In contrast, a substantially high 5 -R2 mRNA levels was found in spinal cord (SC) (Pozzi et al 2003), an observation perfectly in agreement with recent findings that indicate 5 -R2 immunoreactive material in adult rat SC is much higher than those of 5 -R1 (Patte- Mensah et al 2004).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The high V max of 5 -R1 endows it with a great capacity to reduce steroids at 5 , and for this reason 5 -R1 has been associated with purely catabolic actions, protecting neurons from excess of glucocorticoids that may induce apoptotic processes (Mahendroo et al 1997, Poletti et al 1998a. In contrast, a substantially high 5 -R2 mRNA levels was found in spinal cord (SC) (Pozzi et al 2003), an observation perfectly in agreement with recent findings that indicate 5 -R2 immunoreactive material in adult rat SC is much higher than those of 5 -R1 (Patte- Mensah et al 2004).…”
Section: Discussionsupporting
confidence: 91%
“…According to the previous findings observed in the SC (Patte-Mensah et al 2004) the 5 -R2 mRNA levels were not significantly modified two weeks after castration in the prefrontal cortex of female rats. 5 -R2 mRNA is much less regulated by T (5-fold and 26-fold in I and castrated animals, respectively) and DHT (3-fold and 13-fold in I and castrated animals, respectively) in females than in males (Torres & Ortega 2003a).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These include neuroprotection against ischemia and stroke (Cutler, et al, 2005,Djebaili, et al, 2005,Hoffman, et al, 2003,Lapchak, 2004,Meffre, et al, 2007,Shear, et al, 2002,VanLandingham, et al, 2006, recovery of motor function after spinal cord injury (di Michele, et al, 2000,Fiore, et al, 2004,Labombarda, et al, 2006,Patte-Mensah, et al, 2004,Pomata, et al, 2000, regulation of myelination (Chavez-Delgado, et al, 2005,Gago, et al, 2001,Ghoumari, et al, 2005,Ghoumari, et al, 2003,Le Goascogne, et al, 2000,Schumacher, et al, 2000,Schumacher, et al, 2004, proliferation of neuronal stem cells (Suzuki, et al, 2004,Wang, et al, 2005 , neurogenesis in the hippocampus (Keller, et al, 2004,Suzuki, et al, 2004,Wang, et al, 2005, and induction of analgesia (Pathirathna, et al, 2005,Todorovic, et al, 2004. Many of these actions of neurosteroids are discussed in detail in other papers in this issue.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent series of studies, we observed that the rat DH is an active neurosteroidogenic center that contains several sensory neurons expressing the isoenzyme type 2 of 5␣-reductase (5␣-R) and 3␣-hydroxysteroid oxydo-reductase (3␣-HSOR), also called 3␣-hydroxysteroid dehydrogenase (10,11). 5␣-R and 3␣-HSOR are the two key enzymes catalyzing progesterone conversion into dihydroprogesterone (5␣-DHP) and tetrahydroprogesterone (3␣,5␣-THP) or allopregnanolone, which control important functions such as sexual behaviors, neuroprotection, stress, anxiety, analgesia, sleep, and locomotion (12)(13)(14)(15).…”
mentioning
confidence: 99%